ANALISIS KEPUASAN MAHASISWA-MAHASISWI BEASISWA ATLET FUTSAL UNIVERSITAS KRISTEN INDONESIA TERHADAP PELAYANAN LAPANGAN FUTSAL PERSADA HALIM JAKARTA TIMUR - Ahmad Fauzi ejiahmad321@gmail.com; Frangky Yosua Sitorus; Fenny B.N.L. Tobing (Universitas Kristen Indonesia, 2023)
These studies aim to determining level of consumer satisfactions based on performances and interests at the Persada Halim Futsal Field in East Jakarta and to determine what attributes cause customer satisfaction at the Persada Halim Futsal Field in East Jakarta. Data using is source from primarily data obtain from research questionnaires distributed to 86 respondents while secondaries data is obtaining from book or others data source relate to research. Research methodology using by author is descriptive qualitative. For the data analysis technique, the writer uses Importance Performance Analysis, Likert Score, Anova table and Cartesian chart to prove or find out statistical tests. Through this research, it may be known both performances variable and the importance of the level of accuracy of the data through the ANOVA table, it is obtained that n performance = 0.965 and n importance = 0.968. It may be concluding that data from the questionnaire distributed by researcher to the respondents was declared accurate. From the results of the attitude value, the maximum number of attitudes is 287,59 and the minimum number of attitudes is 68.62. And the percentage of attitude value is 88,48% because the percentage of attitude value is more than 80%, so level of customer satisfactions with services of the East Jakarta Persada Halim futsal field. Conclusion is may be drawn base on result of the research above is that the attributes that become the main priority are the availability of air conditioning in every Persada Halim field, several CCTVs are installed at Persada Halim, Persada Halim employees provide special services if there are service problems, Persada Halim employees help for injured consumers. while playing. Keywords: Performance, Satisfaction, Service